Strong at the broken places : voices of illness, a chorus of hope - Cohen, Richard M. (New York : HarperCollins Publishers, 2008)
A testament to living with chronic illness presents the experiences of five individuals who have battled such conditions as ALS, Crohn's disease, and bipolar disorder, offering insight into how their diseases have affected their lives and personal relationships.
The meeting -- Denise Glass: fighting for control -- Reflections: the way we choose to live -- Buzz Bay: keeping the faith -- Reflections: honoring our own separate peace -- Ben Cumbo: facing down demons -- Reflections: quality over quantity -- Sarah Levin: seeking normalcy -- Reflections: staying strong -- Larry Fricks: slashing at stigma -- Reflections: surviving stigma -- Coming together.
Keywords: Chronically ill -- United States -- Biography; People with disabilities -- United States